Design and Simulation of Asynchronous Buck Converter using Fuzzy Logic Controller (FLC) - Hutagalung, Nirmalasari; Dionova, Brainvendra Widi; Hendrawati, Dwiana (Politeknik Negeri Semarang, 2024)
Currently, Indonesia's energy is running out andhas received serious attention so the Government targets thatby 2050 the role of renewable energy will be at least 31%. Thisencourages the production of various alternative energysources that are environmentally friendly and available, suchas solar power plants. However, solar intensity and a dynamicenvironment strongly influence the output power generated bysolar panels. So in this research, an asynchronous buckconverter design using MPPT will be made to track themaximum power point of solar panels with the fuzzy logiccontroller method which will be applied to Monocrystallinesolar panels with a capacity of 300WP. Fuzzy MPPT will adjustthe duty cycle by PWM Arduino Nano on the asynchronousbuck converter to keep reaching the maximum power point.The results show that the developed system can increase powerconversion efficiency and maintain output voltage stabilityunder various operational conditions. The implementation ofFLC as MPPT on Asynchronous Buck Converter successfullyoptimizes the power absorbed from solar panels, thussupporting the reduction of electrical energy consumption fromPLN in the Jakarta Global University student associationsecretariat building. This implementation is expected to be areference for the implementation of a smarter and moresustainable energy management system in the future.